Self-reported sleep pattern, quality and problems among schooling adolescents in Southwestern Nigeria. (2017)
Objective: Understanding sleep patterns and related factors is vital to development in adolescence, but there is a dearth of this information among adolescents in developing countries such as Nigeria. Therefore, this study describes the sleep patterns, problems, and predictors of poor sleep quality among schooling adolescents. Methods: In a cross-sectional study design, 450 adolescents were selected and interviewed about their sleep experience and problems over the preceding one-month period using a validated form with components adapted from the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Data were analyzed using descriptive statistics, c2, and logistic regression model with p set at 0.05. Results: The mean age of respondents was 13.4 ± 1.2 years. Only half (50.2%) had a global PSQI score of <6, suggesting little or no difficulty with sleep. Significantly, a higher proportion of respondents spent a short time in bed before sleep, _15 min among those who had good sleep quality (81.4%) compared with those who had poor sleep quality (65.2%) (p < 0.001). The odds of having poor sleep quality was significantly higher in the subgroup who had _8.5 h sleep than those who had 8.5 h sleep or more (adjusted odds ratio ¼ 4.62; 95% confidence interval ¼ 2.61, 8.17, p < 0.001). Conclusion: Remarkably poor sleep quality exists among schooling adolescents in Ibadan, Nigeria, and sleep problems are prevalent, especially among those with short sleep duration.